2009
DOI: 10.1021/jp900335p
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation on the Electron Transport Path through the Porphyrin Molecules and Chemisorption of CO

Abstract: In this report, we studied the electron transport through cyclic π-conjugated molecules. The model system consists of metalloporphyrin with two thiol groups at either 9,11-substitution (P-connection) or 1,5-substitution (D-connection) which form chemical bonds with gold electrodes. We investigated 10 typical bivalent metals as the metal-molecule-metal junctions using first principle density functional theory and nonequilibrium Green's function calculations. Due to the particular electron transport paths, all m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
60
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 47 publications
8
60
0
Order By: Relevance
“…42 In a micro- scopic porphyrin molecule, we also demonstrated that the electron transport pathway is the one with the lowest energy barrier. 20 One question raised is how to determine the electron transport pathway in present models. Efficient electron transport is dependent on the energy barrier, which is described by barrier height and barrier length.…”
Section: The Electron Transport Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…42 In a micro- scopic porphyrin molecule, we also demonstrated that the electron transport pathway is the one with the lowest energy barrier. 20 One question raised is how to determine the electron transport pathway in present models. Efficient electron transport is dependent on the energy barrier, which is described by barrier height and barrier length.…”
Section: The Electron Transport Pathwaymentioning
confidence: 99%
“…The specific electron transport pathway was also observed in the circular conjugated systems. 19,20 The circular conjugated molecules are promising materials in nanoelectronics. According to the ring size, the circular conjugated molecules can be classified into three catalogs.…”
Section: Introductionmentioning
confidence: 99%
“…The directional dependence of the conductance might arise from different transmission pathways 52,53 and electron hopping within defective parts of MoS 2 -ML. 54 To date, only grain boundaries have been studied in experiment, and our results are consistent with the results reported by the Heinz group.…”
mentioning
confidence: 99%
“…[30,31] Therefore, they may behave differently from other molecular wires with single electron-transport channels. Herein, we focus on the correlation between the diverse electron-transport behaviors and the molecular structures by investigating the conductance of a series of conjugated molecules wired between two Au electrodes.…”
mentioning
confidence: 99%